Description of a new species of Spiralothelphusa Bott, 1968, and redescription of Spiralothelphusa wuellerstorfi (Heller, 1862) (Decapoda: Brachyura: Gecarcinucidae) - Pati, Sameer K.; Mandal, Sudipta; Jaiswal, Deepa (European Journal of Taxonomy, 2022)
A new species of the gecarcinucid freshwater crab genus, Spiralothelphusa Bott, 1968, is described from the Andhra Pradesh State of South India, with supporting data from mitochondrial cytochrome c oxidase subunit I. This brings the number of known species of Spiralothelphusa to seven, five from India and two from Sri Lanka. The identity of S. wuellerstorfi (Heller, 1862) has remained uncertain because the former lectotype designation was not clear. Bott (1968), while designating a male lectotype of S. wuellerstorfi from the Naturhistorisches Museum Wien, Vienna, Austria, had neither stated the catalogue number nor the size of the specimen. It is now difficult to trace the particular lectotype among several paralectotypes of the depository. A new lectotype is, therefore, designated herein for S. wuellerstorfi, and the species is redescribed. The new species, S. andhra sp. nov., has morphological affinities with S. wuellerstorfi, but can be distinguished from the latter species by the shape of the male telson and outer margin of the non-twisted portion of the male first gonopod. Phylogenetic analyses of the molecular data also corroborate their separation. An illustrated identification key is provided for the species of Spiralothelphusa.